The overgrowth of structure-function coupling in premature brain during infancy - Rong Wang; Tianyu Fang; Yue Zhang; Yue Cheng; Chunfang Wang; Yuanyuan Chen; Qiuyun Fan; Xin Zhao; Dong Ming (Developmental Cognitive Neuroscience)
Although the rapid growth of brain structure and function during infancy has been well documented, relatively little is known about how these two developmental processes couple—an aspect that exhibits distinct patterns in adult brain. In this study, the multimodal MRI data from the dHCP database were used to investigate the coupling between brain structure and function in infants, with a particular focus on how prematurity influences this relationship. A similar pattern of the coupling distribution between preterm and full-term infants was identified with coupling index varying across unimodal cortices such as visual and sensorimotor regions and transmodal cortices including default mode network. Notably, a widespread overgrowth of structure-function coupling and a slow developmental trajectory towards full-term infants in preterm infants at term-equivalent age were found. Collectively, the study quantified the development of structure-function relationships in preterm infants, offering new insights into the information transmission processes and developmental patterns of the early-life brain.